REQUEST STRATEGIES USED BY FIVE STREET DANCE GROUPS LEADERS TO MALE AND FEMALE MEMBERS IN THE MEETING - F. S. Prayogo; Herwindy Maria Tedjaatmadja (Kata Kita: Journal of Language, Literature, and Teaching, 2013)
This study entitled “Request Strategies Used by Five Street Dance Group Leaders to Their Male and Female Members in the Meetings” was conducted to know the influence of gender toward the request made by the leaders in the street dance groups’ meetings. The writer observed five young male leaders of five different street dance groups in making request to the male and female members in the meeting. The writer used the theory from Trosborg (1995) to classify the request uttered by the leaders. He found that the leaders mostly used the same request strategy, which is direct strategy to both male and female members in the meetings. The result also showed that the leaders used more indirect strategies, such as mild hints to the female than the male members probably because the leaders tried to be more polite to the female members.